Alcohol and direction vehicle: attitudes in Law academics (Research, Society and Development, 2020)
The objective was to evaluate the behavior of undergraduate Law students, in relation to alcohol consumption and driving. Cross-sectional study with law students from a private educational institution in Aracaju/SE. To assess the socio-demographic and academic profile, and to verify the individuals who drink and drive, questions were elaborated based on the I National Survey on the use of Alcohol, Tobacco and other Drugs, complemented with the Youth Risk Behavior Survey (YRBS). The Alcohol Use Disorders Identification Test (AUDIT) was used to assess the pattern of alcohol consumption. Pearson's chi-square, Pearson's chi-square tests with Monte-Carlo simulation and Fisher's exact test were used. Crude odds ratios were estimated for the variables that obtained p